Tofacitinib benefit‐risk profile in chronic plaque psoriasis. (2nd January 2019) - Strober, B.E.; Gottlieb, A.B.; van de Kerkhof, P.C.M.; Puig, L.; Bachelez, H.; Chouela, E.; Imafuku, S.; Thaçi, D.; Tan, H.; Valdez, H.; Gupta, P.; Kaur, M.; et al.
Summary: Although there are several highly effective treatments for severe psoriasis, many of them have to be given by injection and they are ineffective in some patients. Tofacitinib is a new oral (taken by mouth) drug which inhibits an enzyme, Janus kinase. It has proved beneficial in diseases called rheumatoid arthritis and ulcerative colitis, and its use has been studied in psoriasis. The authors, based in Europe, North and South America and Japan, have reviewed 6 clinical trials assessing the benefits and risks of tofacitinib treatment in patients with moderate or severe plaque psoriasis. The data collected comprise over 5, 000 patient years. Patients received either 5mg or 10mg twice daily and were reviewed after 4 months and after a year. The drug was generally well tolerated, with side effects similar to the "biologic treatments" currently available for moderate to severe psoriasis, although there was a slightly higher rate of herpes zoster (shingles) infection, especially in the higher dose. The higher dose was more effective, and overall there was considerable improvement in the patient's quality of life, with improvement in the appearance of skin and nails and rapid reduction of itching. The authors conclude that the drug is effective and has an acceptable safety profile. As yet there is only one published trial comparing its efficacy with a biologic treatment (etanercept) and further comparisons with established drugs are desirable. However many patients would prefer to take a drug orally rather than by injection; injection reactions are a significant problem with biologic treatments. Abstract : Linked Article: Strober et al. Br J Dermatol 2019;180 :67–75